2004
DOI: 10.1007/s00425-003-1143-z
|View full text |Cite
|
Sign up to set email alerts
|

PCC1 : a merging point for pathogen defence and circadian signalling in Arabidopsis

Abstract: Using a cDNA-array we identified expressed sequence tag 163B24T7 as rapidly up-regulated in Arabidopsis thaliana (L.) Heynh. after pathogen exposure. Detailed expression analysis revealed that the corresponding gene is up-regulated not only after exposure to avirulent Pseudomonas syringae pv. tomato but also to virulent strains. This up-regulation is dependent on functional salicylic acid defence-signalling pathways. Moreover, we found the gene was circadian-regulated, showing peaks of expression at the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 55 publications
4
58
0
1
Order By: Relevance
“…It would thus be conceivable that the observed daytime-dependent differences in P. syringae-induced plant defenses result from the circadian rhythm. On the basis that some genes implicated in plant defense follow a circadian expression pattern, a link between defense and circadian signaling has been established previously (Sauerbrunn and Schlaich, 2004). Examples for such genes are Arabidopsis PCC1 (pathogen and circadian controlled 1) and PAL1 (Sauerbrunn and Schlaich, 2004;Rogers et al, 2005).…”
Section: Discussion Daytime Dependency Of Resistance Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…It would thus be conceivable that the observed daytime-dependent differences in P. syringae-induced plant defenses result from the circadian rhythm. On the basis that some genes implicated in plant defense follow a circadian expression pattern, a link between defense and circadian signaling has been established previously (Sauerbrunn and Schlaich, 2004). Examples for such genes are Arabidopsis PCC1 (pathogen and circadian controlled 1) and PAL1 (Sauerbrunn and Schlaich, 2004;Rogers et al, 2005).…”
Section: Discussion Daytime Dependency Of Resistance Responsesmentioning
confidence: 99%
“…On the basis that some genes implicated in plant defense follow a circadian expression pattern, a link between defense and circadian signaling has been established previously (Sauerbrunn and Schlaich, 2004). Examples for such genes are Arabidopsis PCC1 (pathogen and circadian controlled 1) and PAL1 (Sauerbrunn and Schlaich, 2004;Rogers et al, 2005). The plant circadian clock maintains a relatively constant period, even in the absence of environmental cues such as light (Hotta et al, 2007).…”
Section: Discussion Daytime Dependency Of Resistance Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a small polypeptide PCC1, whose overexpression leads to resistance against Hyaloperonospora arabidopsidis, is under both defense and circadian regulation (Sauerbrunn and Schlaich, 2004), and, recently, a group of genes involved in basal and R-mediated defense was shown to be under the control of CCA1, a core clock component . In the latter study, the central clock oscillator appeared unaffected by H. arabidopsidis infection.…”
Section: B Cinerea Infection Dampens Clock Gene Oscillationsmentioning
confidence: 99%
“…Does this anticipation by the plant of regular abiotic environmental changes extend to anticipation of changes in biotic challenges? Certainly pathogen-inducible genes have been identified that have diurnal and/or circadian rhythms of expression (Molina et al, 1997;Wang et al, 2001;Sauerbrunn and Schlaich, 2004;Weyman et al, 2006). The functional significance of this is not yet clear, as it was also recently demonstrated that under defined environmental conditions, 89% of Arabidopsis transcripts are expressed rhythmically, being regulated by the circadian clock or directly by environmental changes in light or temperature (Michael et al, 2008).…”
Section: Is There Circadian Regulation Of Immunity In Plants?mentioning
confidence: 99%